2019
DOI: 10.1371/journal.pone.0218134
|View full text |Cite
|
Sign up to set email alerts
|

Selection and co-selection of antibiotic resistances among Escherichia coli by antibiotic use in primary care: An ecological analysis

Abstract: Background The majority of studies that link antibiotic usage and resistance focus on simple associations between the resistance against a specific antibiotic and the use of that specific antibiotic. However, the relationship between antibiotic use and resistance is more complex. Here we evaluate selection and co-selection by assessing which antibiotics, including those mainly prescribed for respiratory tract infections, are associated with increased resistance to various antibiotics among … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 38 publications
1
32
1
1
Order By: Relevance
“…Pouwels (2018 and 2019) reported co-selection of resistance to antibiotics associated with prescribing, but did not adjust for possible confounding factors. [19,31] No study has yet demonstrated the concerning rise in resistance we observed in relation to the decreased dispensing of some antibiotics. The explanation for this is not clear.…”
Section: Results In the Context Of Existing Researchmentioning
confidence: 95%
“…Pouwels (2018 and 2019) reported co-selection of resistance to antibiotics associated with prescribing, but did not adjust for possible confounding factors. [19,31] No study has yet demonstrated the concerning rise in resistance we observed in relation to the decreased dispensing of some antibiotics. The explanation for this is not clear.…”
Section: Results In the Context Of Existing Researchmentioning
confidence: 95%
“…In practice, antibiotic use can affect ABR against an antibiotic of a different class. For instance, amoxicillin, which is typically prescribed for respiratory tract infections, is associated with increased trimethoprim and ciprofloxacin resistance in Escherichia coli causing urinary tract infections [69,70]. Conversely, higher nitrofurantoin use was found to be associated with lower levels of trimethoprim and amoxicillin resistance, potentially due to collateral sensitivity or a negative correlation between resistance genes [69].…”
Section: Extension In Space: From One Hospital To National/global Estmentioning
confidence: 99%
“…For instance, amoxicillin, which is typically prescribed for respiratory tract infections, is associated with increased trimethoprim and ciprofloxacin resistance in Escherichia coli causing urinary tract infections [69,70]. Conversely, higher nitrofurantoin use was found to be associated with lower levels of trimethoprim and amoxicillin resistance, potentially due to collateral sensitivity or a negative correlation between resistance genes [69]. Models relating (human) antibiotic consumption to ABR assume that the relationship is not confounded by between-country differences such as in infection prevention and control measures and agricultural antibiotics use.…”
Section: Extension In Space: From One Hospital To National/global Estmentioning
confidence: 99%
“…Moreover, within England, the reported number of macrolide-resistant BSI for gram-positive bacteria increased between 2014 and 2018, even though prescribing for macrolides decreased in both hospitals and primary care [3]. Sustained or increased resistance in the absence of antibiotic exposure could be a result of multiple factors, including resistance genes imposing a negligible fitness cost, continued use of other antibiotics that are co-selecting for resistance, or lagged effects of antibiotic reductions [5].…”
mentioning
confidence: 99%